Participating in a community-based participatory research module: A reflective inquiry. (22nd September 2020) - Hally, Ruth; Murphy, Aisling; O'Connell, John; Robinson, Sarah; Pyrz, Katarzyna; Burns, Kenneth; O'Mahony, Catherine
Abstract : page_276 other This commentary piece, using a narrative inquiry frame, explores the experiences of five individuals who came together to participate in a community-based participatory research (CBPR) module. Owing to the short time frame of this accredited module, when the module was live, a particular focus was directed towards dialogical techniques to build trust and respect within the group and subsequently generate potential research questions. The inaugural experience of collaborating on a CBPR module stimulated unique feelings, reflections and learnings for participants, many of which took time to surface. This article aims to make sense of those experiences to support those wishing to engage in CBPR initiatives.